Expression of SMADs in orthotopic human endometrium, ovarian endometriosis, and endometriotic lesions in a murine model - Yuri Kadota; Takeshi Kato; Kana Kasai; Takako Kawakita; Misaki Murayama; Akari Shinya; Hikari Sasada; Sachiko Katayama; Mari Nii; Shota Yamamoto; Hiroki Noguchi; Kou Tamura; et al. (Endocrine Journal)
Activin A promotes the development of endometriotic lesions in a murine model of endometriosis, and the immunohistochemical localization of phosphorylated suppressor of mothers against decapentaplegic homolog 2/3 (pSMAD2/3) complex in endometriotic lesions has been reported. Activin may therefore be involved in the development and proliferation of endometriotic cells via the SMAD signaling pathway. However, few detailed reports exist on SMAD7 expression in endometriosis. The purpose of this study was to investigate the expression of pSMAD2/3 or pSMAD3 and SMAD7 in the orthotopic human endometrium, ovarian endometriosis, and endometriotic lesions in a murine model and the effect of activin A on pSMAD2/3 and SMAD7 expression. We established an endometriosis murine model via the intraperitoneal administration of endometrial tissue and blood from donor mice. Activin A was intraperitoneally administered to the activin group. We immunohistochemically evaluated orthotopic endometria, ovarian endometriotic tissues, and endometriotic lesions in the murine model followed by western blotting. We found that pSMAD3 and SMAD7 were expressed in ovarian endometriosis and orthotopic endometria from patients with and without endometriosis. In the murine model, endometriotic lesions expressed pSMAD2/3 and SMAD7 in the activin and control groups, and higher SMAD7 expression was found in the activin group. To the best of our knowledge, this study is the first to show that SMAD7 expression is upregulated in endometriosis. In conclusion, these results suggest that activin A activates the SMAD signaling pathway and promotes the development of endometriotic lesions, thus identifying SMAD7 as a potential therapeutic target for endometriosis.